Epidemiology, Pathophysiology, and Management of Native Atrioventricular Valve Regurgitation in Heart Failure Patients - Martin, Anne-Céline; Bories, Marie-Cécile; Tence, Noemie; Baudinaud, Pierre; Pechmajou, Louis; Puscas, Tania; Marijon, Eloi; Achouh, Paul; Karam, Nicole (Frontiers in Cardiovascular Medicine, 2021)
Atrioventricular regurgitation is frequent in the setting of heart failure. It is due to atrial and ventricular remodelling, as well as rhythmic disturbances and loss of synchrony. Once atrioventricular regurgitation develops, it can aggravate the underlying heart failure, and further participate and aggravate its own severity. Its presence is therefore concomitantly a surrogate of advance disease and a predictor of mortality. Heart failure management, including medical therapy, cardiac resynchronization therapy, and restoration of sinus rhythm, are the initial steps to reduce atrioventricular regurgitation. In the current review, we analyse the current data assessing the epidemiology, pathophysiology, and impact of non-valvular intervention on atrioventricular regurgitation including medical treatment, cardiac resynchronization and atrial fibrillation ablation.